2020
DOI: 10.1088/1755-1315/580/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

Application research on slope deformation monitoring and earthwork calculation of foundation pits based on UAV oblique photography

Abstract: The stability of foundation pit slopes is a key concern during the construction of foundation pits. The deformation and instability of slopes will pose a major threat to the safety of foundation pits construction. Based on the foundation pit project of Shenzhen Dapeng People’s Hospital, this study uses DJI phantom 4 RTK drone to collect oblique photography data of the foundation pit in different periods, reconstructs high-precision 3D virtual models through the Bentley ContextCapture software and generates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…This technology employs a fixed base station and advanced algorithms to correct GNSS signal errors in real time, as depicted in Figure 3. Despite their higher cost, the accuracy afforded by RTK drones was demonstrated by Jiang et al [62] while evaluating earthwork volume changes, as they managed to reconstruct the 3D model with an average RMS (Root Mean Square) accuracy of 2-3 cm. When comparing the use of non-specialized low-cost drones with specialized geodetic class drones, Filkin et al [38] intriguingly found no significant difference in results when using them for a waste disposal site volume estimation.…”
Section: Drone Photogrammetrymentioning
confidence: 99%
“…This technology employs a fixed base station and advanced algorithms to correct GNSS signal errors in real time, as depicted in Figure 3. Despite their higher cost, the accuracy afforded by RTK drones was demonstrated by Jiang et al [62] while evaluating earthwork volume changes, as they managed to reconstruct the 3D model with an average RMS (Root Mean Square) accuracy of 2-3 cm. When comparing the use of non-specialized low-cost drones with specialized geodetic class drones, Filkin et al [38] intriguingly found no significant difference in results when using them for a waste disposal site volume estimation.…”
Section: Drone Photogrammetrymentioning
confidence: 99%
“…Following Jiang et al [11], height difference and slope monitoring was conducted to monitor the progress and to analyze deformation of earthwork slope. During excavation, slopes deform and even become unstable, posing a risk.…”
Section: Height Difference and Slope Monitoringmentioning
confidence: 99%
“…In addition, the area is excavated downwards to tens of meters deep, posing a risk of landslides. The slope must be monitored to avoid landslides and accident to workers [11]. Moreover, with a depth of tens of meters, contractors deal with several types of soil with different characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Yi et al [19] recently conducted a study that could effectively analyze changes in earthwork through oblique photographic surveys of UAV. This study explored the use of UAV oblique photography for the deformation monitoring of the foundation pit slope and calculation of earthwork volume changes.…”
Section: Introductionmentioning
confidence: 99%